Wat is 'n gereformeerde liturgie? - J. Janse van Rensburg (Acta Theologica)
The current debate on a reformed liturgy is driven by opposition. On the one hand, some protagonists for renewal embrace anything new that works, while on the other hand traditionalists reject attempts to renew the liturgy, arguing that such efforts go against the reformed liturgy. The question, however, is raised: “What is a reformed liturgy?” The article endeavours to indicate principles for  renewal, based on reformed theology and not on the reformed tradition.